BEYOND BIRDS’ CONSERVATION: ENGAGING COMMUNITIES FOR THE CONSERVATION OF URBAN GREEN SPACES - Bhakti, Tulaci; Lodi, Marina P.; Marujo, Leonardo S.; Pena, João Carlos [UNESP]; Rodrigues, Marcos (Aves Argentinas / Asociacion Ornitologica del Plata, 2023)
Urban green spaces are important for bird conservation functioning not only as a buffer against the impacts of human actions on their surroundings, but also bringing benefits to humans, such as the impro-vement of climatic conditions and a more intimate contact with nature. In this point of view, we describe, in three sections, how ornithological research in a peri-urban vegetation patch in a tropical metropolis culminated in an environmental protection movement. This vegetation patch consists of a mosaic of typical phytophysiog-nomies from the transition zone between two biodiversity hotspots: Cerrado and Atlantic Forest. Even though its vegetation presents characteristics that indicate high degradation, the region still harbors 108 bird species (threatened and endemic species included), suggesting that notwithstanding the adverse impacts, the area presents characteristics of resilience to shelter the local biodiversity. Given these findings, we discuss the potential of this urban green space for scientific research, environmental education, and birdwatching. We highlight the possibility of influencing community engagement in the conservation of the area, whether for the preservation of charismatic species or for leisure and educational activities. By bridging the gap between academia and so-ciety we can assist in the conservation of urban green spaces, especially in a region that presents high social environmental vulnerability.
MÁS ALLÁ DE LA CONSERVACIÓN DE LAS AVES: INVOLUCRANDO A LAS COMUNIDADES PARA LA CONSERVACIÓN DE LOS ESPACIOS VERDES URBANOS
Keywords: citizen participation; environmental education; social environmental; urban ecology